The Effect of Using Small Groups’ Style On Learning Some Fundamental Skill In Basketball For Second Grade Secondary Scholl Students - Abed, sharifaa; Faris, Laith (Journal of Physical Education, 2019)
The importance of the research lies in the effect of using small groups in learning some fundamental basketball skills in second grade secondary school. The researchers used the experimental method on (24)  second grade students from Al Qurtas secondary school for boys divided into two equal groups (12) controlling and (12) experimental groups. After applying the teaching program, the data was collected and treated using the proper statistical operation to conclude that using small group style have a great effect on learning some fundamental basketball skills.